How valid are student perceptions of teaching quality across education systems?. (December 2022) - Herbert, Benjamin; Fischer, Jessica; Klieme, Eckhard
Abstract: In an international context, teaching quality is often assessed via student surveys. Yet, there is little empirical evidence for the validity of students' perceptions of teaching quality across education systems. Following an argumentative validation approach, we evaluate the reliability, stability, and international comparability of students' perceptions of teaching quality as well as their predictivity on student outcomes. Based on longitudinal data from six education systems our main findings include that student perceptions of teaching quality are 1) reliable on the class level, 2) stable between two measurements, and 3) metric invariant across education systems, yet 4) their effects on achievement, interest, and self-efficacy vary between the aspects of teaching quality and education systems. Our study provides first substantial empirical findings for the validity of student perceptions across education systems and points towards culture-specific differences in the effectiveness of teaching. Highlights: Student perceptions are a valid measure for teaching quality across countries. We present empirical evidence regarding reliability, stability and predictivity. Student perceptions of teaching quality are metric invariant across six countries. Effects of teaching quality on student outcomes are culture-specific.